Sculpture in Gotham art and urban renewal in New York City - Bogart, Michele H. (London Reaktion Books Ltd, 2018)
Public sculpture is a big draw in today's cities. Nowhere is this more the case than in New York, where urban art has become synonymous with the municipal `brand', highlighting the metropolis as vibrant, creative, tolerant, orderly and, above all, safe. 'Sculpture in Gotham' tells the story of how the City of New York became committed to public art patronage, beginning in the mid-1960s. In that moment of political turbulence, cultural activists and City officials for a time shifted away from traditional monuments, and joined forces to sponsor ambitious sculptural projects as an instrument for urban revitalization.
Includes bibliographical references (pages 229-269) and index.
Keywords: Public sculpture -- New York City; Sculpture -- New York City; Urban renewal -- New York City